Tire rubber-derived contaminants 6PPD and 6PPD-quinone reduce attachment and outgrowth of trophoblast spheroids onto endometrial epithelial cells - Jong Geol Lee; Seon Min Lee; Moonjung Hyun; Jeong Doo Heo (Ecotoxicology and Environmental Safety)
N-(1,3-Dimethylbutyl)-N′-phenyl-p-phenylenediamine (6PPD), a synthetic additive widely used in the rubber industry, and its oxidized product 6PPD-quinone (6PPDQ), have garnered widespread attention as an emerging hazardous chemicals owing to their potential detrimental effects on aquatic ecosystem and human health. The effects of 6PPD and 6PPDq on the female reproductive tract, especially embryo implantation, remain unknown and were investigated in this study. We used the spheroid attachment and outgrowth models of BeWo trophoblastic spheroids and Ishikawa cells as surrogates for the human blastocyst and endometrial epithelium, respectively. Treatment with the chemicals for up to 48 h decreased the viability of the cells in a dose- and cell line-dependent manner (20–100 μM 6PPD and 10–100 μM 6PPDQ for both the cell lines). At a noncytotoxic concentration, exposure of Ishikawa cells to 1 and 10 μM 6PPD reduced the attachment of BeWo spheroids and further inhibited their invasion and outgrowth on the endometrial epithelial monolayer. A similar result was observed in 1 μM 6PPDQ-exposed groups. Gene expression profiling of 6PPD- and 6PPDQ-exposed endometrial epithelial cells revealed that both 6PPD and 6PPDQ differentially regulated a panel of transcript markers toward overall downregulation of receptivity and invasion. The study provides the first proof of the adverse effects of 6PPD and 6PPDQ on human endometrial receptivity and trophoblast invasion during the window of implantation, warranting the need for further in vivo and clinical studies.